BEYOND PUNTA DEL ESTE. A LOOK AT BICHROMATE USE IN THE CUBAN ROCK ART - Gutiérrez Calvache, Divaldo (2010)
t is produced a documentary record of the Cuban rock art stations where its have been used two colors or tones in its implementation. The record is facing the problem until the level of site and its features, by proposing a simple taxonomic model for define, organize and classify the different variants of the use of bichromate in our country. Finally, its been made a brief comment on relations between the bichromate, overlap and the time criteria developed at the base of this problem, allowing us to ensure that it is necessary to enhance and develop our analytical models, due to this problem that we are approaching is complex and can only be dealt with complex methods of investigation.